Effects of pre-cracks on both initiation and propagation of re-bar corrosion in pure carbon dioxide - L’Hostis Valérie; Hiep Dang Vu; François Raoul (EPJ Web of Conferences, 2013)
This paper deals with effects of pre-cracks on both initiation and propagation of reinforcement steel corrosion due to carbonation. The ring shaped mortar samples with 8 mm steel bar inside were cracked with different crack widths ranging from 12 micrometers to 600 micrometers and then subjected to carbon dioxide environment for different terms to assess the carbonation profile in cracks and along the interface between steel and concrete, damaged by the internal pressure applied to the ring samples. After carbonation of interface, ring samples were submitted to wetting-drying cycles to study the propagation of corrosion and the effect of corrosion products on healing and then repassivation of steel bar or corrosion cracks development. Results show that irrespective of width of cracks, the carbon dioxide reaches the interface between steel and mortar and propagates along this interface. The samples then subjected to wetting-drying cycles exhibit corrosion development all along the interface,the appearance of oxides does not lead to create corrosion cracks for the duration of the experiments.